Atrial fibrillation management during septal myectomy for hypertrophic cardiomyopathy: A systematic review. (January 2022) - Seco, Michael; Lau, Jonathan CL; Medi, Caroline; Bannon, Paul G
Introduction: Atrial fibrillation is common in patients with hypertrophic cardiomyopathy, and significantly impacts mortality and morbidity. In patients with atrial fibrillation undergoing septal myectomy, concomitant surgery for atrial fibrillation may improve outcomes. Methods: A systematic review was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. All studies reporting the outcomes of combined septal myectomy and atrial fibrillation surgery were included. Results: A total of 10 observational studies were identified, including 644 patients. Most patients had paroxysmal atrial fibrillation. The proportion with prior unsuccessful ablation ranged from 0 to 19%, and preoperative left atrial diameter ranged from 44 ± 17 to 52 ± 8 mm. Cox–Maze IV (n = 311) was the most common technique used, followed by pulmonary vein isolation (n = 222) and Cox–Maze III (n = 98). Patients with persistent or longstanding atrial fibrillation more frequently received Cox–Maze III/IV. Ranges of early postoperative outcomes included: mortality 0 to 7%, recurrence of atrial tachyarrhythmias 4.4 to 48%, cerebrovascular events 0 to 1.5%, and pacemaker insertion 3 to 21%. Long-term data was limited. Freedom from atrial tachyarrhythmias at 1 year ranged from 74% to 96%, and at 5 years from 52% to 100%. Preoperative predictors of late atrial tachyarrhythmia recurrence included left atrial diameter >45 mm, persistent or longstanding preoperative atrial fibrillation and longer atrial fibrillation duration. Conclusion: In patients with atrial fibrillation undergoing septal myectomy, the addition of ablation surgery adds low overall risk to the procedure, and likely reduces the risk of recurrent atrial fibrillation in the long term. Future randomised studies comparing septal myectomy with or without concomitant AF ablation are needed.